REPORT OF THE TRAJECTORY AND CONTRIBUTIONS OF SOCIAL SPORTIVE PROJECTS WITH CHILDREN AT STATE OF RISK: A CASE STUDY IN THE FEEVALE UNIVERSITY CENTER (Fiep Bulletin - online, 2014)
The social sportive projects are a tool for social transformation. Thus, it was aimed to report the trajectory of social sportive projects with children at risk associated to the Feevale University Center; and verify their contributions during the period from 2000 to 2004. As methodology, the descriptive narrative search was used, having as the primary source of information the experiences and the scientific production originated from the projects. The social sportive projects linked to the institution are the "Children of Canudos" and the Social Futsal projects. They were created in 2000 and 2004, respectively. Both work with children at risk, being the main risk identified in the first project the destructured family, which leads the child to the context of the street and thus enjoying all the risks that it offers. Three types of contributions were identified. The first is related to the scientific production, having 89 works published; three research projects were identified as related to the projects, being the most recent one active and associated with a master dissertation. The second contribution is the quality of vocational training, where the academic, active in the projects, has to perform an accurate reading of the social reality of their students and an adaptation of activities for the formation of a critic citizen/participant in the society. Finally, there is a social contribution to the students, parents and the community. Initially they were resistant, but as the credibility of the work was conquered, it was observed that the children amplified their knowledge beyond their reality; the school directors saw improvement in the learning process and in respect to other people and; the parents have become proud of their children. However, it was also identified problems that compromise the effectiveness of the work. It is concluded that the work must be continued in this context, encouraging scientific research and considering their results to qualify the social sportive projects for the benefit of the community studied.
Keywords: Physical Education; Social Sportive Projects; Children at Situation of Risk